Determinants of KB duration and desired number of children among women of reproductive age in Banjarangkan District, Klungkung Regency - Putri, Ni Putu Risma Diana; Marhaeni, A.A.I.N. (Priviet Social Sciences Journal, 2024)
This study aims to: 1) Analyze the influence of women’s employment status, sex preference, the Governor’s instruction on Bali’s Krama Bali family planning (KB) program, and women’s education on the KB duration of women of reproductive age; Analyze the influence of women’s employment status, sex preference, the Gover- nor’s instruction on Bali’s Krama Bali family planning program, women’s education, and KB duration on the desired number of children among women of reproductive age; 3) Analyze the indirect influence of women’s employment status, sex preference, the Governor’s instruction on the Krama Bali family planning program, and women’s education on the desired number of children through KB duration among women of reproductive age. This research utilizes a quantitative method with an associative approach. The sample size is 99 respondents, consisting of women of reproductive age, selected using Snowball Sampling and Accidental Sampling techniques. Data collection was carried out through observation, structured interviews, and in-depth interviews. Path analysis was employed for data analysis. The results of the study indicate: 1) Women of reproductive age who are employed have longer contraceptive use compared to those who are unemployed in Banjarangkan District, Klungkung Regency; 2) Women’s education has a significantly positive impact on KB duration among women of reproductive age in Banjarangkan District, Klungkung Regency; Sex preference and the Governor’s instruction on the Krama Bali family planning program have a significantly negative impact on KB duration among women of re- productive age in Banjarangkan District, Klungkung Regency; 4) Employed women of reproductive age desire fewer children compared to those who are unemployed in Banjarangkan District, Klungkung Regency; 5) Women’s education and KB dura- tion have a significantly negative impact on the desired number of children among women of reproductive age in Banjarangkan District, Klungkung Regency; 6) Sex preference and the Governor’s instruction on the Krama Bali family planning pro- gram have a positive impact on the desired number of children among women of reproductive age in Banjarangkan District, Klungkung Regency; 7) Women’s em- ployment status, sex preference, the Governor’s instruction on the Krama Bali family planning program, and women’s education influence the desired number of children among women of reproductive age through KB duration in Banjarangkan District, Klungkung